Measuring negative sense of place: Israeli settlers’ forced migration - Shamai, Shmuel (GeoJournal, 2018)
This research focused on negative sense of place, a subject that has not adequately considered in the literature. The main purpose of the study was to examine whether it possible to classify the different feelings of negative sense of place, arrange them in hierarchal order, and test them empirically. The aim of the research is to contribute to better understanding of negative sense and methods for examining it. Interviews were held with Israeli settlers who had been evacuated from the Gaza Strip and the West Bank (in 2005) against their will; the research was conducted 3 years after their resettlement. The findings indicate that their perceptions of their places of relocation were negative, but at a relatively low level of (negative) intensity.